2004
DOI: 10.1080/1024533042000205487
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Polymorphism in Egyptian Children with Lymphomas

Abstract: (1) The susceptibility to NHL is related to HLA-DRB1 *0403 and *1301 and HLA-DQB1 *0501,* 0201 and *0301. (2) The susceptibility to HD is related to HLA-DRB1 *0403 and *1202 and HLA-DQB1 *0604, *0201 and *0203. (3) HLA-DRB1 *1302 and HLA-DQB1 *0502 and *0602 may confer protection to NHL. (4) Different HLA alleles may have a role in patients with both groups of lymphoma and further study is needed to better define the possible prognostic value of different HLA associations in patients with lymphomas regarding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…DRB1*09 allele in our data is in agreement with significant increase of the DRB1*09 allele in the data from Thai patients with NHL [15]. However, our data is different from the study on Egyptian children patients with NHL, the HLA-DRB1*0403 and DRB1*1301 alleles, and the HLA-DQB1*0501, HLA-DQB1*0201, and HLA-DQB1*0301 alleles were significantly increased while the HLA-DRB1*1302, DQB1*0502, and DQB1*0602 alleles were significantly decreased [16]. This result may suggest that the observed differences in the association of HLA class I and class II antigens between the different studies may be due to the different ethnic groups.…”
Section: Discussioncontrasting
confidence: 85%
“…DRB1*09 allele in our data is in agreement with significant increase of the DRB1*09 allele in the data from Thai patients with NHL [15]. However, our data is different from the study on Egyptian children patients with NHL, the HLA-DRB1*0403 and DRB1*1301 alleles, and the HLA-DQB1*0501, HLA-DQB1*0201, and HLA-DQB1*0301 alleles were significantly increased while the HLA-DRB1*1302, DQB1*0502, and DQB1*0602 alleles were significantly decreased [16]. This result may suggest that the observed differences in the association of HLA class I and class II antigens between the different studies may be due to the different ethnic groups.…”
Section: Discussioncontrasting
confidence: 85%
“…We found significant increase in the frequency of HLA DRB1*0403 and *1202 and DQ131*0604, *0201 and *0203 alleles which may confer suscepilibity (Al-Tonbary et al, 2004). Similar results were reported by Klitz et al (1994) who reported a significant association of HLA class II alleles with Hodgkin's lymphoma and Harty et al (2002) who reported that the DRB1*1501 allele is related to the development of familial Hodgkin's lymphoma particularly the familial nodular sclerosis type.…”
Section: Familial Incidence and Genetic Susceptibilitysupporting
confidence: 80%
“…In our hospital it was previously reported that HLA-DRB1*03011, HLADRB1*01 and HLA-DRB1*07011 alleles confer susceptibility to poststreptococcal acute glomerulonephritis (Bakr et al 2007), steroid sensitive nephritic syndrome (Bakr et al 1998) and steroid resistant nephrotic syndrome (Bakr et al, 2005), respectively. Similarly HLA-DRB1*0403 & *1301 were associated with non Hodgkin lymphoma and HLA-DRB1*0403 & *1202 alleles were associated with Hodgkin disease in Egyptian children (Al-Tonbary et al, 2004). Moreover HLA-DRB1*04 was found to be significantly associated with hepatocellular carcinoma in Egyptian adults (El-Chennawi et al 2008).…”
Section: Discussionmentioning
confidence: 95%